How Does the Mind Grow? Cross-Cultural Intuitive Theories of Mental Development - Meng, Xianwei; Oguni, Ryuji; Nishina, Kuniyuki; Murakami, Taro; Mizuno, Yuka; Wang, Jinjing (Jenny) (Psychological Science, 2026)
How does the mind grow? Despite centuries of philosophical and psychological inquiry, little is known about how ordinary people intuitively conceptualize mental development. Across six countries (Australia, Japan, Mexico, South Africa, the United Kingdom, and the United States), adult participants reported their intuitions about mental development by indicating when they think various mental capacities first emerge. Across tasks and cultures, intuitions about mental development were consistently organized along two dimensions: an earlier-developing perceptual and experiential dimension (e.g., seeing, fear, hunger, pain) and a later-developing reflective and evaluative dimension (e.g., reasoning, beliefs, self-restraint, pride). Competing models were ruled out, showing that this structure is unique to lay beliefs about mental development. These dimensions also aligned with participants’ intuitions about the origins of mental capacities within a nature–nurture framework. Together, the findings reveal a consistent cross-cultural pattern for reasoning about mental development and illuminate the intuitive architecture of mind perception.